2003
DOI: 10.1590/s0004-282x2003000100022
|View full text |Cite
|
Sign up to set email alerts
|

A case of primary spinal myoclonus: clinical presentation and possible mechanisms involved

Abstract: -Spinal myoclonus is a rare movement disorder characterized by myoclonic involvement of a group of muscles supplied by a few contiguous segments of the spinal cord. Structural lesions are usually the cause, but in primary spinal myoclonus the etiology remains unknown. We present the case of a 26-year-old woman with cervical spinal myoclonus in which both clinical and electromyographic findings pointed to the segment C1-C3 as the origin of the myoclonus. Laboratorial examinations were normal and no structural l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 18 publications
0
11
0
2
Order By: Relevance
“…Another case report described a 26-year-old female with segmental C1–C3 spinal myoclonus in whom injection of botulinumtoxin A into the infrahyoid and cervical paraspinal muscles stopped the movements. The effect lasted for 5 months 63. In a recent review article on propriospinal myoclonus, the authors reported 20 patients from the world literature who had responded to botulinum toxin treatment 64…”
Section: Resultsmentioning
confidence: 99%
“…Another case report described a 26-year-old female with segmental C1–C3 spinal myoclonus in whom injection of botulinumtoxin A into the infrahyoid and cervical paraspinal muscles stopped the movements. The effect lasted for 5 months 63. In a recent review article on propriospinal myoclonus, the authors reported 20 patients from the world literature who had responded to botulinum toxin treatment 64…”
Section: Resultsmentioning
confidence: 99%
“…Proposed mechanisms included the loss of inhibitory function of local dorsal horn interneurons, abnormal hyperactivity of local anterior horn neurons, aberrant local axons re-excitations and loss of inhibition from supra-segmental descending pathways [1,5,6]. Demyelinated axons can be abnormally hyper-excitable and can display spontaneous discharges, which alone, or driven reflexibly, could lead to myoclonus [7].…”
Section: Discussionmentioning
confidence: 99%
“…loss of inhibitory function of local dorsal horn inter-neurons, abnormal hyperactivity of local anterior horn neurons, aberrant local axons re-excitations and loss of inhibition from supra-segmentar descending pathways [2]. …”
Section: Discussionmentioning
confidence: 99%
“…Though structural lesions are usually found in spinal myoclonus, the pathophysiology remains speculative. But there is evidence that various possible mechanisms can be involved: loss of inhibitory function of local dorsal horn interneurons, abnormal hyperactivity of local anterior horn neurons, aberrant local axons re-excitations and loss of inhibition from suprasegmentar descending pathways [2]. …”
Section: Introductionmentioning
confidence: 99%